Paracrine Interactions of Thyroid Hormones and Thyroid Stimulation Hormone in the Female Reproductive Tract have an Impact on Female Fertility - Stavreus-Evers, Anneli (Frontiers in Endocrinology, 2012)
Thyroid disease often causes menstrual disturbances and infertility problems. Thyroid hormone (TH) acts through its receptors, transcription factors present in most cell types in the body. Thyroid stimulating hormone (TSH) stimulates TH synthesis in the thyroid gland, but seems to have other functions as well in the female reproductive tract. The receptors of both TH and TSH increase in the receptive endometrium, suggesting that they are important for implantation, possible by influencing inflammatory mediators such as LIF. The roles of these receptors in the ovary need further studies. However, it is likely that the thyroid system is important for both follicular and embryo development. The association between thyroid disease and infertility indicate that TH and TSH affect the endometrium and ovary on the paracrine level.